PENGARUH SOCIAL MEDIA BRAND ENGAGEMENT TERHADAP WILLINGNESS TO PAY A PREMIUM PADA LUXURY BRANDS DI KALANGAN MASYARAKAT JABODETABEK - Wijayanti, Bella; Arafah, Willy (Universitas Dharmawangsa, 2025)
PENGARUH SOCIAL MEDIA BRAND ENGAGEMENT TERHADAP WILLINGNESS TO PAY A PREMIUMPADA LUXURY BRANDS DI KALANGAN MASYARAKAT JABODETABEKABSTRACTThe luxury skincare industry in Indonesia is experiencing rapid growth with the increasing use of social media and consumers need for quality products with an exclusive image. Under these conditions, brand engagement on social media is a key strategy to build perceived value and encourage consumers' willingness to pay more. This study aims to examine the influence of Social Media Brand Engagement, Consumer Empowerment and Parasocial Interactions on Willingness to Pay Premium. This research uses a quantitative approach with an online survey method through a questionnaire. Data was collected from 102 respondents who live in the Jabodetabek area who are active social media users and have experience or interest in luxury skincare products. The data analysis technique uses Covariance-Based Structural Equation Modeling (CB-SEM) with the help of AMOS software. The test results show that Social Media Brand Engagement has a positive and significant influence on Consumer Empowerment and Parasocial Interactions. However, Consumer Empowerment and Parasocial Interactions do not have a significant influence directly on Willingness to Pay Premium. The implications of these findings suggest that brands need to focus digital strategies on increasing social engagement to create emotional value and strengthen perceptions of exclusivity.Keywords: Social Media Brand Engagement, Parasocial Interactions, Willingness to Pay a Premium, Consumer Empowerment, Luxury Skincare